A Glossary of Common Logging Terms - Asthana, M. N. (Indian Forester, 1963)
Literature on Logging was scarce in India till recently and many of the logging terms are not well understood by the average reader. Even the official glossary is not complete in this respect. To make modern logging terms better understood, a list of the more common terms together with their definitions and meanings has been prepared and given.